COMPARISON OF THE ORIGINAL (PLAVIx) AND GENERIC (CLAPITAx) CLOPIDOGREL ON PLATELET AGGREGATION: ObSERVATIONAL STUDY - A. S. Skotnikov; Zh. M. Sizova; A. N. Baglikov; O. G. Rozhnova; N. I. Novitsky (Российский кардиологический журнал, 2018)
Aim. To compare antiplatelet activeness of the original clopidogrel and its generic, and to evaluate the routine practice of antiplatelet drugs intake by clinically stable patients aiming prevention of atherothrombosis.Material and methods. Total number of patients that have been taking clopidogrel: 186, of those at outpatient stage 54 on original clopidogrel, the rest 132 on generic. Adenosindiphosphate-induced activeness was measured in two groups (n=57) taking consequently Plavix and Clapitax before replacement of the drug and 14 days after.Results. At interchange of the drug in group 1 (Clapitax to Plavix) and group 2 (Plavix to Clapitax) the grade of achieved effect remained, and in group 2 it showed additional non-significant decrease. Adverse events related to antiplatelet therapy were not registered. At in-patient stage, 117 patients had an interchange of the drug (incl. several times) of original clopidogrel to its various generics (n=65), and vice versa (n=52), that was related to a range of routine reasons, of those patient and relatives preferences, specifics of drug supply in a clinic.Conclusion. The found equal residual reactivity of the platelets after Clapitax and Plavix intake in two groups witness on therapeutical equivalence of the drugs.